Discourse on the Authority of Sunnah and Hadith in the Perspective of Daniel W. Brown - Maulana Iban Salda; Syamsul Rijal; Abdul Mugni; Taslim HM. Yasin (IAIN Ponorogo, 2022)
Islam in Western thought has a very bad brand image and relative image. One Orientalist named Daniel W. Brown criticized the hadith and sunnah of the Prophet Muhammad for their nonconformity with textual and contextual passages. The study aimed to find out specifically about Brown's understanding of Hadith and Sunnah, factors that influenced Brown in criticizing both. The method approach chosen in this study is the qualitative method, while the data used is sourced from literature studies in the form of works written by Brown himself and other people's works on Brown's work and thoughts. The results of the study mentioned that Brown is an orientalist who is an expert in the field of historians who explore and study hadith and Sunnah using data, and the propositions of the Qur'an and hadith. Brown criticized the Sunnah and hadith not for personal gain or by order, but he criticized them because he was an expert in history. Brown mentioned found two tendencies of understanding the content in hadith, namely, the restriction of traditionalist and modern scriptures.